Legal Analysis of the Blocking of Customer Accounts by PT Bank Mandiri TBK from the Perspective of Customer Legal Protection (Study of Decision Number 112/PDT.G/2022/PN.YYK) - Alya Puspita Juliasari; Dhiva Aurora Pramhesta Dharma; Elda Septi Darmayanti; Friska Nova Wijaya Siagian; Muhamad Daud Hidayatulloh; Salma Ayu Nurmala; Luthy Yustika (Jurnal Multidisiplin Sahombu, 2026)
Blocking customer accounts is one of the administrative measures that banks can take in order to apply the principles of prudence and risk control. However, this authority is not absolute, as it has the potential to limit the civil rights of customers if carried out without a clear legal basis and valid procedures. This study aims to examine the legal regulations regarding the authority of banks to block accounts by PT Bank Mandiri Tbk in the Yogyakarta District Court Decision Number 112/Pdt.G/2022/PN.Yyk with the principle of legal protection for banking customers. The research method used is normative juridical research with a legislative approach and a case approach. The primary legal sources include Law No. 10 of 1998 concerning Banking, Law No. 8 of 1999 concerning Consumer Protection, Financial Services Authority Regulations concerning Consumer Protection in the Financial Services Sector, and Court Decisions. Secondary legal materials were obtained from literature, scientific journals, and opinions of banking law experts. The results of the study show that the authority of banks to block accounts can only be exercised if there is a valid legal basis and must be accompanied by the principles of transparency, proportionality, and accountability. This study concludes that PT Bank Mandiri Tbk is not in accordance with the principles of customer legal protection and incurs legal liability for the bank.